2014
DOI: 10.3109/00365521.2014.983156
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive characterization of graft steatosis after liver transplantation

Abstract: Modern noninvasive liver graft assessment frequently detects hepatic steatosis, which is associated with graft fibrosis, components of the metabolic syndrome and recipient PNPLA3 rs738409 genotype, especially in ALC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Comparable results were recently obtained by Karlas et al . in a study performed in transplanted patients, which demonstrated that graft recipients bearing the PNPLA3 p.148M allele are at risk of increased VTCE‐quantified liver steatosis and stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…Comparable results were recently obtained by Karlas et al . in a study performed in transplanted patients, which demonstrated that graft recipients bearing the PNPLA3 p.148M allele are at risk of increased VTCE‐quantified liver steatosis and stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…In this direction, the development of diagnostic algorithms with the use non-invasive tools is warranted. Karlas et al [ 70 ] demonstrated that modern non-invasive liver graft assessments such as hepatic ultrasound and transient elastography might be able to properly detect both steatosis and graft fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Karlas et al evaluated post‐LT steatosis by TE using CAP measurements in a population of 204 patients who underwent LT, 50% of whom were transplanted for alcoholic cirrhosis and only 2% transplanted for NASH. At the time of the study, CAP was not available using the XL probe and thus only the M probe was used.…”
Section: Methodsmentioning
confidence: 99%